Younger age is associated with cardiovascular pathological phenotype of severe COVID-19 at autopsy - Giugni, Fernando R.; Duarte-Neto, Amaro N.; da Silva, Luiz Fernando F.; Monteiro, Renata A. A.; Mauad, Thais; Saldiva, Paulo H. N.; Dolhnikoff, Marisa (Frontiers in Medicine, 2024)
Introduction COVID-19 affects patients of all ages. There are few autopsy studies focusing on the younger population. We assessed an autopsy cohort aiming to understand how age influences pathological outcomes in fatal COVID-19. Methods This study included autopsied patients, aged 6 months to 83 years, with confirmed COVID-19 in 2020–2021. We collected tissue samples from deceased patients using a minimally invasive autopsy protocol and assessed pathological data following a systematic approach. Results Eighty-six patients were included, with a median age of 55 years (IQR 32.3–66.0). We showed that age was significantly lower in patients with acute heart ischemia (p = 0.004), myocarditis (p = 0.03) and lung angiomatosis (p < 0.001), and significantly higher in patients with exudative diffuse alveolar damage (p = 0.02), proliferative diffuse alveolar damage (p < 0.001), lung squamous metaplasia (p = 0.003) and lung viral atypia (p = 0.03), compared to patients without those findings. We stratified patients by their age and showed that cardiovascular findings were more prevalent in children and young adults. We performed principal component analysis and cluster of pathological variables, and showed that cardiovascular variables clustered and covariated together, and separated from pulmonary variables. Conclusion We showed that age modulates pathological outcomes in fatal COVID-19. Younger age is associated with cardiovascular abnormalities and older age with pulmonary findings.